2022
DOI: 10.1029/2021ja030160
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Beaming of Io Decametric Emissions: A Remote Diagnostic to Probe the Io‐Jupiter Interaction

Abstract: We investigate the beaming of 11 Io‐Jupiter decametric (Io‐DAM) emissions observed by Juno/Waves, the Nançay Decameter Array, and NenuFAR. Using an up‐to‐date magnetic field model and three methods to position the active Io Flux Tube (IFT), we accurately locate the radiosources and determine their emission angle θ from the local magnetic field vector. These methods use (a) updated models of the IFT equatorial lead angle, (b) ultraviolet (UV) images of Jupiter's aurorae, and (c) multi‐point radio measurements. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
4
9
0
Order By: Relevance
“…For instance, comparing in more details the simulations that account for the lead angle and refractions effects (Figure 8c) with the circularly polarized radio emission from RPWS indicates that the early part of the radio emission arc (from 22:00:00 to 22:15:00) are better reproduced with electrons with lower energies, that is, 5 keV, while the center and end of the arc are better reproduced with electrons with energies ranging from 10 to 15 keV. It is worth noting here that Lamy et al (2022) showed that, in the case of Io, the electrons energy derived from radio emission analysis is variable as a function of the moon longitude. It is not surprising here to observe that in order to reproduce the arc in the time-frequency plane, the energy of the electrons must vary with time (i.e., the longitude of the moon).…”
Section: Application To Modeling Of the Moon-induced Decametric Emissionmentioning
confidence: 74%
See 3 more Smart Citations
“…For instance, comparing in more details the simulations that account for the lead angle and refractions effects (Figure 8c) with the circularly polarized radio emission from RPWS indicates that the early part of the radio emission arc (from 22:00:00 to 22:15:00) are better reproduced with electrons with lower energies, that is, 5 keV, while the center and end of the arc are better reproduced with electrons with energies ranging from 10 to 15 keV. It is worth noting here that Lamy et al (2022) showed that, in the case of Io, the electrons energy derived from radio emission analysis is variable as a function of the moon longitude. It is not surprising here to observe that in order to reproduce the arc in the time-frequency plane, the energy of the electrons must vary with time (i.e., the longitude of the moon).…”
Section: Application To Modeling Of the Moon-induced Decametric Emissionmentioning
confidence: 74%
“…It is worth noting here that Lamy et al. (2022) showed that, in the case of Io, the electrons energy derived from radio emission analysis is variable as a function of the moon longitude. It is not surprising here to observe that in order to reproduce the arc in the time‐frequency plane, the energy of the electrons must vary with time ( i.e., the longitude of the moon).…”
Section: Application To Modeling Of the Moon‐induced Decametric Emissionmentioning
confidence: 88%
See 2 more Smart Citations
“…The radio emission from the exomoon interaction could also be a time variable similar to the variability seen in the Jupiter-Io emission. Furthermore, the emission due to the interaction between Io and Jupiter is also highly beamed (e.g., Queinnec & Zarka 1998;Zarka et al 2004;Ray & Hess 2008;Lamy et al 2022). Similar beaming is expected from exomoon-exoplanet interactions.…”
Section: Time Variable and Beamed Emissionmentioning
confidence: 75%